2003
DOI: 10.2116/analsci.19.537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Electrical Degradation Products of 4-Chlorophenol in Water

Abstract: The electrical decomposition of 4-chlorophenol in water was examined with iridium dioxide doped on a titanium electrode. A number of electrical degradation products of 4-chlorophenol, such as hydroquinone and chlorohydroquinone via the addition of hydroxyl radicals, and dichlorophenol through addition of chlorine radical, were observed as major products. Moreover, hydroxylated chlorobiphenylethers, hydroxylated dibenzo-p-dioxin/furans and hydroxylated chlorobiphenyls formed by a dimerization process during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Poerschmann et al reported the formation of similar compounds upon the Fenton oxidation of 2-chlorophenol under substoichiometric conditions. It should be considered that oxidative coupling reactions are not exclusive of Fenton-like oxidation because they are generally promoted by • OH radicals, and thus, the formation of condensation byproducts from poly-CPs occurs in other advanced oxidation processes, like electrooxidation, ozonation , or UV/H 2 O 2 oxidation. , In this sense, Hirvonen et al detected a variety of chlorinated dimers formed both by UV/H 2 O 2 andby the ozonation of chlorophenols. The m / z values of the detected dimers (288, 304, 322, 340, 354) were very similar to those obtained in our work.…”
Section: Resultsmentioning
confidence: 99%
“…Poerschmann et al reported the formation of similar compounds upon the Fenton oxidation of 2-chlorophenol under substoichiometric conditions. It should be considered that oxidative coupling reactions are not exclusive of Fenton-like oxidation because they are generally promoted by • OH radicals, and thus, the formation of condensation byproducts from poly-CPs occurs in other advanced oxidation processes, like electrooxidation, ozonation , or UV/H 2 O 2 oxidation. , In this sense, Hirvonen et al detected a variety of chlorinated dimers formed both by UV/H 2 O 2 andby the ozonation of chlorophenols. The m / z values of the detected dimers (288, 304, 322, 340, 354) were very similar to those obtained in our work.…”
Section: Resultsmentioning
confidence: 99%
“…There are few references that quantify the formation of dioxins and furans during the application of AOPs to synthetic aqueous samples containing chlorinated organics and complex matrices such as landfill leachates. , With regard to the use of electro-oxidation as remediation technology, Hong et al presented the decomposition of 4-chlorophenol using an iridium dioxide anode working at 400 A m –2 with a mixture of H 3 PO 4 and NaH 2 PO 4 as the electrolyte . They identified the presence of hydroxylated dibenzodioxin/furans and hydroxylated chlorobiphenyls as minor byproducts after 60 min of treatment, but without their quantification.…”
Section: Resultsmentioning
confidence: 99%
“…To identify nonpolar small metabolites in ECMs, gas chromatography/mass spectrometry (GC/MS) was carried out as described by Hong et al . (2003). Briefly, samples dissolved in n‐hexane were applied to an Agilent 6890 GC coupled to an Agilent 5973N mass spectrometer (Palo Alto, CA, USA) equipped with a DB‐5MS silica capillary column (Agilent 6890N, Palo Alto, CA, USA) of dimensions 60 m × 0.25 mm × 0.25 μm (length × i.d.…”
Section: Methodsmentioning
confidence: 99%